Shift in the LHC Higgs diphoton mass peak from interference with background - Martin, Stephen P. (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
The Higgs diphoton amplitude from gluon fusion at the LHC interferes with the continuum background induced by quark loops. I investigate the effect of this interference on the position of the diphoton invariant mass peak used to help determine the Higgs mass. At leading order, the interference shifts the peak towards lower mass by an amount of order 150 MeV or more, with the precise value dependent on the methods used to analyze and fit the data.